A Study on Human Resource Accounting Model - Dr. Sasmita Mohanty, Manaswini Patnaik, (Design Engineering, 2021)
This article is an attempt towards critically evaluating the models of human resource accounting that are used by private and public companies in India. Using a questionnaire survey method on a series of managerial stuff in five public sector and five private sector companies. The study makes a report on the HRA executions which go after bythe firms. Additionally using secondary sources company’s annual reports. The nature of the study is qualitative and explanatory based on secondary data which arecollected from different article, journals, websites. The study also tracks down the particular model used by this set up companies in assessing their human assets. covers some models that any HR professional should be familiar with. It provides an in-depth assessment of particular models used by the companies in valuating and measuring their human resource. The findings show that why Lev Schwartz model is used by many companies. There is a fundamental difference and gap in the usage of this model.